Transforming Construction Management in Peru: The Role of BIM in Innovation and Efficiency. - Pacheco, Alex Abelardo (2024)
In the contemporary landscape of construction project management, the strategic integration of Building Information Modeling (BIM) methodology has emerged as a fundamental avenue to improve operational efficiency. This study evaluates the feasibility and effectiveness of the implementation of the BIM methodology in improving the management of construction projects in construction companies in Peru. Using an applied approach underscored by a quantitative and correlational nonexperimental design, a comprehensive survey was administered to 415 workers. This survey focused on evaluating the dimensions of BIM (3D, 4D, and 5D), as well as the fundamental facets of project management that encompass planning and execution. The results reveal that 47% of respondents highlighted deficiencies within the 3D BIM dimension, indicating potential challenges in visualizing and understanding the design. Likewise, 49% of participants highlighted deficiencies within the 4D BIM dimension, shedding light on issues related to time coordination and strategic planning. Around 57% expressed reservations about the 5D BIM dimension, highlighting the complexities surrounding accurate cost estimation and financial management. The synthesis of these revelations underscores an urgent call for specific interventions to rectify these specific areas. This involves investing in cutting-edge BIM technology tools and the simultaneous provision of targeted training programs for stakeholders to increase their multi-dimensional view of BIM. Ultimately, the study results drive innovation, thus opening the prospect of a more sustainable and streamlined construction industry